Role Modelling in Medical Education (Community Based Medical Journal, 2025)
Forming professional and humanistic physicians for the 21st century is a great challenge for medical educators worldwide. Role modelling by the medical teachers can be positive or negative and the challenge for us is to reduce the influence of negative role modelling. Positive role modelling has been defined as the process whereby faculty members exhibit knowledge, attitude, and skills; demonstrate and articulate expert thought processes; and manifest positive professional behaviour and characteristics. Role modelling is undoubtedly important in professional character formation and enhancing moral values among medical students, interns and residents who will serve the nation in future. In medical colleges and higher medical institutions of our country, some of the faculties from basic sciences and mostly clinical teachers consciously or unconsciously become positive and influential role models for the students, interns and residents. It is imperative that we as medical teachers and our institutions will come forward so that the educational environment in both undergraduate and postgraduate education supports such positive role modelling in medical education and training. Role modelling takes place in three interrelated educational environments which are the formal, informal, and hidden curriculum. Formal curriculum is the planned and structured part of medical education, including lectures, textbooks, and assessments, as we teach and train medical ethics and professionalism in regular curriculum. The informal curriculum is defined as an unspecified, predominantly ad hoc and highly interpersonal form of teaching and learning that takes place among and between faculty and students. The hidden curriculum has been defined as a set of influences that function at the level of organizational and culture, influenced by its people and environment. In this review, we tried to explore the impact of role modelling as well as the characteristics of positive role models and how role modelling could be integrated in our curriculum.CBMJ 2025 July: vol. 14 no. 02 P:208-213